2011
DOI: 10.1080/02626667.2011.555766
|View full text |Cite
|
Sign up to set email alerts
|

Yield–reliability analysis for rural domestic water supply from combined rainwater harvesting and run-of-river abstraction

Abstract: Yield-reliability analysis for rural domestic water supply from combined rainwater harvesting and run-of-river abstraction. Hydrol. Sci. J. 56(2), 238-248. AbstractIn many rural areas, reticulated water supply from large water resources schemes does not exist and many households obtain water from groundwater (GW), rainwater harvesting (RWH), run-of-river (ROR) flow, or combinations of these. While comprehensive yield-reliability analysis for large water resource systems is the norm, typical rural water supply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Daily time step simulation of RWH systems has been used to provide data for generalizing storage-yield-reliability relationships [26][27][28] and for other analyses [22,[37][38][39][40]. Simulation also forms the basis of most RWH modelling tools [9].…”
Section: Simulation Analysismentioning
confidence: 99%
“…Daily time step simulation of RWH systems has been used to provide data for generalizing storage-yield-reliability relationships [26][27][28] and for other analyses [22,[37][38][39][40]. Simulation also forms the basis of most RWH modelling tools [9].…”
Section: Simulation Analysismentioning
confidence: 99%
“…This shows that the domestic water requirements can only be met at a high level of supply service at relatively low LAS compared to the recommended LAS by DWAF (2004) to be met at these LAS, then other sources of supply would be required to supplement the ROR supply. For example, Ndiritu et al (2011a, b) showed that integration of RWH and ROR supply improves yield and reliability up to 96% (1:25) for a period of 9 months. This underscores the need to integrate all of the available sources of water to supply the water requirements in water-scarce rural areas at the recommended LAS.…”
Section: If Q T(t) ≥ D + Lfr (T) Then Ds (T) = Dmentioning
confidence: 99%
“…Over the past few years, it has become quite clear that in large parts of South Africa, and particularly in rural areas, people experience acute water shortages. Reticulated water supply from storage reservoir systems is not common and less capital-intensive set-ups, including boreholes, run-of-river (ROR) supply and rainwater harvesting (RWH), serve as the main sources of water (Ndiritu et al, 2011a). In rural areas of the country, unregulated ROR abstractions are common.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rainwater harvesting has been identified in many areas as an economically feasible solution to reduce strain on current water supply systems and provide optimal water quality. In addition, it is seen as an adaptive measure to address climate change effects on precipitation variability (Ndiritu et al, 2011). Rainwater harvesting has been an appealing alternative for rural populations, especially where a centralized water supply system is not viable (Barron, 2009).…”
Section: Rainwater Harvestingmentioning
confidence: 99%